Family firms and internationalization‐governance relationships: Evidence of secondary agency issues - Singla, Chitra; Veliyath, Rajaram; George, Rejie (Strategic Management Journal, 2014)
This article documents that blockholders with both ownership and management control in family firms have different goals compared to blockholders with only ownership (but no management) control. We theorize and find evidence that family controlled and family managed ( FCFM ) firms negatively moderate the relationships between internationalization and governance mechanisms, while family controlled and nonfamily managed ( FCNFM ) firms do not. The findings indicate that family owners in FCFM firms have greater opportunities to reap private benefits of control indicating the presence of secondary (principal‐principal) agency problems, while these problems are mitigated in FCNFM firms. In emerging economies like India where family firms are ubiquitous, they highlight the need to recognize differing blockholder influences on internationalization‐governance relationships and to develop more nuanced theorizing for understanding them . Copyright © 2013 John Wiley & Sons, Ltd.